Conceptualizing Climate Justice - Haque, Mohammad Aynal (Journal of Climate Policy, 2024)
Purpose: The key objective of this study is to conceptualize climate justice. Methodology: The study employs a qualitative systematic analysis of published articles focused on climate justice, and analyzes the various attributes within existing definitions of climate justice. The study analysis is based on secondary resources assessed through openly accessible documents, journals, and libraries. Findings: The study finds that climate justice is used in various contexts "” academia and social movement world "” by scholars and organizations to achieve mainly three outcomes: outcome of procedural justice, physical or material outcome, and policy outcome. The lack of consensus on what exactly this concept means, leads to inconsistencies in its application and further confusion. Findings here point to the weakness of global climate governance in defining such an important concept while pursuing climate change actions. Unique Contribution to Theory, Practice, and Policy: While climate justice is often discussed at a global level, it is equally important to conceptualize it at the local level. In this regard, this study proposes a minimal definition of climate justice, which could be used to avoid a high extension of the concept, in general, both in academia and the social movement world.